Social Imaginaries and Embryonic Design Practices in the Work of Jose Rodrigo de Vivero in the Savannas of the South of Bolivar - Martinez Osorio, Pedro Arturo [UNESP]; Da Cruz Landim, Paula [UNESP]; Ferreira Barata, Tomas Queiroz [UNESP] (Univ Nac Colombia, Sede Medellin, 2019)
Some aspects of the relationship between architecture and the first manifestations of design in the construction of an imaginary of modernization in the context of the Savannas of the South of Bolivar what is now known as the department of Sucre, Colombia, are presented. An urban history built from the critical analysis of the discourse in press of the time and semi structured interviews with key characters. Some social representations and urban imaginaries identified in that historical context are examined to understand their relationship with the appearance of the ideas of a modern architecture, and the incipient development of the design practice as an engine of change in two cities of the Colombian Caribbean. It highlights the work of the architect Jose Rodrigo De Vivero, a practice that contrasts with the univocal origins raised by the official historiography of architecture in Colombia. Its exercise is evidence of the approaches on the origins of design in Colombia, as a historically motivated phenomenon, distanced from technological and industrial aspects of the country's economy.
Keywords: Modern architecture; history of design; design in Latin America; design in the Colombian Caribbean; Imaginaries